A framework for technology transfer success factors: validation for the Graphene4Life project. Issue 2 (2nd April 2020) - Chiș, Diana-Maria; Crișan, Emil Lucian
Abstract : Purpose: The purpose of this paper is to develop a theoretical framework for technology transfer success factors from a technology provider viewpoint and to test this framework considering the perceptions of graphene researchers from a Romanian research project (Graphene4Life). Design/methodology/approach: The authors conducted a literature review and a case study with three units of analysis. Semi-structured face-to-face interviews and content analysis were used. Findings: The five-category framework for technology transfer success factors from a technology provider viewpoint, which portrays success factors in an expansive way from technology to the market (technology, organization, context, collaboration and customer absorptive capacity factors), is confirmed by the qualitative analysis, while new factors in all categories are discovered. Research limitations/implications: The results are limited given the qualitative nature of this research. The extrapolation of the results to other technologies and contexts is a scientific challenge. Originality/value: In this paper, the authors develop, based on a detailed literature review, a framework for technology success factors from a technology provider viewpoint, which classifies technology transfer success factors in an expansive way from technology to the market (technology, organization, context, collaboration and customer absorptive capacity factors). Technology itself is settled as the foundation of the framework, underlining the need for a technology-driven technology transfer process. In comparison to existing frameworks that analyze technology transfer success factors, the present framework is a more complex one, covering all facets of the technology process. The new factors discovered through the qualitative analysis are also an important contribution of this research.